Feverfew (Tanacetum parthenium L.): A systematic review - Pareek, Anil; Suthar, Manish; Rathore, Garvendra S.; Bansal, Vijay (Pharmacognosy Reviews)
Feverfew (Tanacetum parthenium L.) (Asteraceae) is a medicinal plant traditionally used for the treatment of fevers, migraine headaches, rheumatoid arthritis, stomach aches, toothaches, insect bites, infertility, and problems with menstruation and labor during childbirth. The feverfew herb has a long history of use in traditional and folk medicine, especially among Greek and early European herbalists. Feverfew has also been used for psoriasis, allergies, asthma, tinnitus, dizziness, nausea, and vomiting. The plant contains a large number of natural products, but the active principles probably include one or more of the sesquiterpene lactones known to be present, including parthenolide. Other potentially active constituents include flavonoid glycosides and pinenes. It has multiple pharmacologic properties, such as anticancer, anti-inflammatory, cardiotonic, antispasmodic, an emmenagogue, and as an enema for worms. In this review, we have explored the various dimensions of the feverfew plant and compiled its vast pharmacologic applications to comprehend and synthesize the subject of its potential image of multipurpose medicinal agent. The plant is widely cultivated to large regions of the world and its importance as a medicinal plant is growing substantially with increasing and stronger reports in support of its multifarious therapeutic uses.
Keywords: Anti-inflammatory; migraine; parthenolide; Tanacetum parthenium